The United Kingdom's Experience with Inflation Targeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews the first five years' experience with inflation targeting in the United Kingdom. It concludes that inflation performance was not significantly different under inflation targeting than predicted by a VAR model estimated in the period prior to participation in the exchange rate mechanism (ERM). Both short- and long-term interest rates were lower than predicted, however, which is consistent with the interpretation that some gains in credibility were achieved under the inflation targeting regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet